EFFECT OF NON DENTAL GLASS FIBER ORIENTATION ON TRANSVERSE STRENGTH OF DENTAL FIBER REINFORCED COMPOSITE - Abdulghani Ali Khalil; Widowati Siswomiharjo; Siti Sunarintyas (Universitas Gadjah Mada, 2016)
FRC is widely used in dentistry especially for dental bridges construction. E glass fiber is commonly used because it has good properties and good bonding with polymers. Its availability is limited and its price quite expensive in Indonesia. Non dental glass fiber is available in Indonesia with lower price. The aim of this research was to evaluate the effect of non dental glass fiber orientation on transverse strength of dental FRC. Non dental glass fiber (HJ, China) with two orientations (Roving and Woven roving), Flowable composite (CharmFil Flow, DenKist, Korea) , Silane coupling agent (Monobond S, Ivoclar Vivadent, Liechtenstein) and distilled water. 24 specimens of non dental glass FRC, divided into 2 groups. The specimens was immersed in water for 24 hours and 7 days. The data were analyzed by Independent sample T-test. T-test analysis showed that for transverse strength with 24 hours water immersion there was a significant difference between the two orientation groups (p< 0.05). The data of 7 days immersion there was no statistical difference between the groups (p> 0.05). In conclusion: there was different transverse strength between roving and woven roving orientation in dental FRC.